2009
DOI: 10.1111/j.1600-6143.2009.02893.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiply Resistant Gram-Positive Bacteria: Vancomycin-Resistant Enterococcus in Solid Organ Transplant Recipients

Abstract: Epidemiology and Risk Factors Enterococcus is a commonly isolated microorganism in transplant patients, especially after liver and kidney transplantation (1). The incidence of vancomycin-resistant enterococci (VRE) has increased both in the nontransplant (2-4) and transplant settings (5-7). VRE colonization was 4% and 55% (6,8-10) and of infection between 4% and 11% (1,7). The majority of VRE infections occur within the first month following transplantation, although late infections have also been described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 80 publications
(123 reference statements)
1
8
0
Order By: Relevance
“…We identified many known risk factors for VRE infection following liver transplantation in our group of LTRs with DNSE infection, including ICU admission, prolonged hospitalization, renal failure and need for hemodialysis, prolonged operative time, need for reoperation, and biliary strictures or leaks. Interestingly, although choledochojejunostomy is an established risk factor for VRE infection , the majority (64%) of patients in this cohort underwent duct‐to‐duct choledochocholedochostomy as the biliary anastomotic technique. The median length of hospitalization for liver transplantation surgery in the group was 31 days, which is significantly longer than the median 8 days length of hospitalization for liver transplantation at our center ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified many known risk factors for VRE infection following liver transplantation in our group of LTRs with DNSE infection, including ICU admission, prolonged hospitalization, renal failure and need for hemodialysis, prolonged operative time, need for reoperation, and biliary strictures or leaks. Interestingly, although choledochojejunostomy is an established risk factor for VRE infection , the majority (64%) of patients in this cohort underwent duct‐to‐duct choledochocholedochostomy as the biliary anastomotic technique. The median length of hospitalization for liver transplantation surgery in the group was 31 days, which is significantly longer than the median 8 days length of hospitalization for liver transplantation at our center ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study of patients admitted to an institution in anticipation of liver transplantation documented a 44% rate of acquisition of VRE colonization during the index hospitalization , and 2 other studies have demonstrated an approximate 10% incidence of VRE infection in LTRs . Clinical factors associated with VRE infection in the setting of liver transplantation are well established and include intensive care unit (ICU) admission, prolonged hospitalization, renal failure, need for hemodialysis, cytomegalovirus (CMV)‐positive donor, and surgical factors such as prolonged operative time, choledochojejunostomy, need for reoperation, and biliary strictures or leaks . VRE infection is associated with increased mortality after liver transplantation, with reported mortality ranging from 9% to 48% .…”
mentioning
confidence: 99%
“…As a consequence of significant health care exposure antimicrobial-resistant pathogens (methicillinresistant S aureus [MRSA], vancomycin-resistant Enterococcus [VRE], extended spectrum b-lactamase [ESBL] -producing gram-negative organisms) are encountered with increased frequency in transplant recipients. [18][19][20][21][22][23][24][25] In addition, antimicrobial prophylaxis and prior treatment episodes can markedly alter an individual's commensal flora. Thus a heightened awareness of organisms less frequently encountered is required and in certain circumstances empiric therapy should take these organisms into consideration (eg.…”
Section: Early Posttransplantation Periodmentioning
confidence: 99%
“…Surgery, the use of catheters/devices, hospitalization in the intensive care unit, and exposure to broad‐spectrum antibiotics can lead to multidrug‐resistant infections ( Table 2 ). 11 , 12 , 13 Patients awaiting transplantation may also become colonized with these organisms. Antibiotics are given perioperatively to prevent surgical‐site infection, and clinicians should be aware of the recent microbiology history of potential SOTRs and individualize prophylaxis accordingly.…”
Section: Bacterial Infectionsmentioning
confidence: 99%